Allicin Infused Virgin Coconut Oil with Antibacterial Potential - Mohd Sukri Ahmad,; Munirah Mansor Pahmi,; Nur Afiefah Mohd Indera@Ramlee,; Mohd Ismail, Nurul Izzati (Multidisciplinary Applied Research and Innovation, 2023)
The production of allicin infused  soap was aimed to be an alternative to commercial available medicated soaps which contain high in chloroxylenol. High chloroxylenol content is toxic and harmful whihc may be lethal to humans at high concentration. Synergistic effect of Allicin and VCO are contributing to the antibacterial activity. The extraction of allicin was done by using ultrasonication method and was infused in the VCO and undergo saponification process to produce soap (S2). Soap with no allicin was used as a negative control (S1). The performance of both S1 and S2 were determine through its physical, chemical and biological properties. Method that have been used to determine its physical properties are foam stability test and sensory evaluation test. For chemical properties, moisture content, pH and free alkali content test were done whereas antibacterial property of the soap was executed using the disk diffusion test to study its biological characteristic. The disk diffusion test was done on gram-negative and -positive bacterial which were Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) respectively. For its physical property, it was found that both S1 and S2 have good foam stability(~ 97%). In terms of sensory preference, it was found that S2 smell is unfavourable as it contains allicin originated from garlic.  The chemical analysis found that S1 and S2 have alkaline pH (~9.00) and contain sufficient amount of free alkali (~0.8%) within the recommended range. Both S1 and S2 has low moisture content (~ 13%) due to its high VCO content. Interestingly, the addition of allicin in S2 increased its antibacterial effect on E. coli as the formation of inhibition zone was 10 times larger compared to S1. It is concluded that allicin infused soap is a potential substitute to readily available antibacterial soap with comparable physical, chemical and biological properties.